‘Gamma’ band oscillatory response to chromatic stimuli in volunteers and patients with idiopathic Parkinson’s disease - Sannita, Walter G. (2009)
The signal structure of the responses to equiluminant chromatic and achromatic (contrast) stimuli was studied in normal volunteers and patients with mild to moderate idiopathic Parkinson’s disease. Visual stimuli were full-field (14 × 16 deg) achromatic or equiluminant (red-green or blue-yellow) sinusoidal gratings at 2 c/deg and 90% contrast presented in onset-offset mode. The signal was processed offline by DFT and factor analysis was performed in the frequency domain. The conventional VEPs to chromatic onset stimuli showed a monophasic negative wave, while the response to offset stimuli was comparable in shape to the on-/offset achromatic responses; latencies were longer and amplitudes higher than those of responses to contrast stimulation. In patients, latencies were longer than in controls after achromatic and (to a lesser extent) red-green stimulations, but not after blue-yellow stimulation; amplitudes were comparable in all stimulus conditions. In healthy subjects, two non-overlapping factors accounted for the ~2-30.0 Hz and ~25.0-50.0 Hz signal components (representative of the low-frequency VEP and gamma oscillatory responses, respectively); the frequency of the ~25.0-50.0 Hz factor was lower after color than after contrast stimulation. The same factor structure was identified in patients, but the peak frequency of the factor on gamma activity was higher than in controls and did not vary with color-opponent stimulation. These observations indicate that stimulus-related gamma activity originates in cortex irrespective of the activated (magno-, parvo-, or konio-cellular) visual pathway, consistent with the suggested role in the phase coding of neuronal activities. Some dopaminergic modulation of gamma activity is conceivable.